GLOBALISATION CHALLENGES TO INDONESIA'S LEADING ECONOMIC SECTORS: RESILIENCE, COMPETITIVENESS, AND ADAPTATION STRATEGIES - Loso Judijanto (CV. ADIBA AISHA AMIRA, 2025)
This study discusses the challenges faced by Indonesia's main economic sectors in facing globalisation, particularly in relation to resilience and competitiveness. Global market openness has created various external pressures such as price fluctuations, changes in international trade policies, and competition from imported products, which have an impact on national economic resilience. On the other hand, globalisation also opens up opportunities through wider access to export markets, foreign investment, and the adoption of new technologies. Therefore, this study highlights various adaptation strategies that are needed, such as product diversification, technological innovation, improving the quality of human resources, strengthening infrastructure, and protecting intellectual property rights. With the active role of the government, the private sector, and the community, especially MSMEs, Indonesia is expected to be able to strengthen the resilience and competitiveness of its economic sectors so that they can survive and thrive amid increasingly fierce global competition. The method used is a comprehensive literature review of current and relevant sources.